Worlds of Journalism: Journalistic Cultures Around the Globe, Thomas Hanitzsch, Folker Hanusch, Jyotika Ramaprasad and Arnold S. de Beer (eds) (2019). Issue 1 (1st June 2020) - Bebawi, Saba
Worlds of Journalism: Journalistic Cultures Around the Globe, Thomas Hanitzsch, Folker Hanusch, Jyotika Ramaprasad and Arnold S. de Beer (eds) (2019)New York: Columbia University Press, 448 pp., ISBN 978-0-23118-643-8, p/bk, $35.00, ISBN 978-0-23118-642-1, h/bk, $105.00, ISBN 978-0-23154-663-8, e/bk, $34.99